Corner Detection of Hand Gesture - Linghua Li; Lili Zhang (Institute of Advanced Engineering and Science, 2012)
This paper studies the methods of corner detection of hand gesture, and mainly introduces the orthogonal three-direction chain code (3OT) and uses it in corner detection of hand gesture. The study is discussed from four aspects: the techniques used in corner detection, the techniques of Freeman chain code, the main idea of 3OT, the process of corner detection with 3OT and the experiments on corner detectors used for hand gesture images of 26 letters in American Sign Language are described in detail. Experiment results show that the 3OT has well performance with exact corner detection rate and least false corner’s number. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1646